ANALISIS PROGRAM LITERASI MEMBACA 15 MENIT MELALUI CERITA SEKOLAH UNTUK TIMUR DALAM MENINGKATKAN DISIPLIN BELAJAR SISWA SEKOLAH DASAR - Zahiroh, Najma; Diba Catur Putri, Fara; Anggraeni Maharbid, Dian; Amelia, Decenni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The 15-Minute Reading Literacy Program through School Stories for the East is one of the elementary school's efforts to foster a reading culture while improving students' learning discipline. This study aims to analyze the program's implementation and its impact on elementary school students' learning discipline. The research method used was descriptive qualitative. Data collection techniques included observations of the implementation of the 15-minute reading literacy activities in class and interviews with class teachers and literacy assistant teachers. The data obtained were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the 15-minute reading literacy program through School Stories for the East was implemented routinely before learning activities began and was able to shape positive student habits, such as punctuality, learning focus, and compliance with class rules. In addition, teachers played an important role in guiding, motivating, and supervising students during the activity. This program made a positive contribution to improving elementary school students' learning discipline, although several obstacles were still encountered, such as differences in reading interests and limited variety of reading materials. Thus, the 15-minute reading literacy program through School Stories for the East can be used as an effective strategy to improve student learning discipline in elementary schools.